Sistem Informasi Persuratan Berbasis Website Studi Kasus di SMAN 1 Dramaga - Septian, Ihsan; Jaenudin, Jejen; Eosina, Puspa (Jurnal Etnik: Ekonomi-Teknik, 2023)
Letters are an important means of communication in every institution, including at SMAN 1 Dramaga. Unfortunately, letter management at the school is still done manually. Therefore, a web-based letter management information system was designed to help manage and process letter data efficiently and organized. The letter information system can accelerate the letter management process and avoid damage to letters that are stored for too long. A Letter Information System is required to improve letter management performance with timely letter issuance. The system development method used is the SDLC (System Development Life Cycle) method. Data collection methods include observation, interviews, and heritage studies. With a web-based information system, it can improve and facilitate letter management performance, timely letter issuance, and avoid damage to letters that are stored for too long. The result makes it easy to store letters centrally in a database that can be accessed again.